2020
DOI: 10.21609/jsi.v16i1.929
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of the Business Process Maturity Model as a Proposed Architectural Planning of Business Model Concept

Abstract: This research is a part of previous research which succeeded in producing business model architecture planning, the purpose of this research is to develop previous research using business model maturity measurement methods as a proposed business model architecture planning concept. By taking the same case study theme as Tiara Payung Putra (TPP) company. TPP is known as a distributor company in cooperation with Pertamina's (Bulk LPG Filling and Filling Station). TPP's main business activity is to distribute goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The research methodology used in this study is shown in Figure 1 Research Stages [24,25]. A) Literature Study -comprehending the problem and determining the scope and objectives of the research.…”
Section: Methodsmentioning
confidence: 99%
“…The research methodology used in this study is shown in Figure 1 Research Stages [24,25]. A) Literature Study -comprehending the problem and determining the scope and objectives of the research.…”
Section: Methodsmentioning
confidence: 99%
“…Penelitian sebelumnya mengenai manajemen proses bisnis dan BPOMM dilakukan oleh beberapa peneliti dengan melakukan studi literatur ataupun survey proses implementasi manajemen proses bisnis maupun status BPOMM dalam organisasi di beberapa negara, pada penelitian tersebut dilakukan Survei perbedaan penerapan Businsess Process Oriented (BPO) di perusahaan di dua negara, Slovenia dan Kroasia, yang terdiri dari beberapa item praktik Businsess Process Oriented (BPO) kritis yang diidentifikasi dengan menganalisis 15 kerangka kerja dari beberapa penelitian sebelumnya dan sebuah kuesioner dengan 53 item didistribusikan [4]. Pada penelitian [5] Desain arsitektur bisnis yang sukses memungkinkan mengintegrasikan aktivitas bisnis yang penting. Ini juga menunjukkan bahwa arsitektur bisnis adalah salah satu faktor kunci dalam menentukan seberapa baik TI memenuhi tujuan bisnis.…”
Section: Gambar 11 Tahapan Level Maturityunclassified
“…Kajian ini akan fokus pada penyusunan rencana pembangunan dengan menggunakan cetak biru teknologi informasi untuk memenuhi visi dan misi Desa Klingan sebagai pedoman perencanaan pengembangan sistem dan teknologi informasi untuk memenuhi kebutuhan masyarakat [7]. Pada penelitian [8] Desain arsitektur bisnis yang sukses memungkinkan mengintegrasikan aktivitas bisnis yang penting. Ini juga menunjukkan bahwa arsitektur bisnis adalah salah satu faktor kunci dalam menentukan seberapa baik TI memenuhi tujuan bisnis.…”
unclassified